2019
DOI: 10.1021/jacs.9b01717
|View full text |Cite
|
Sign up to set email alerts
|

Porous Molecular Conductor: Electrochemical Fabrication of Through-Space Conduction Pathways among Linear Coordination Polymers

Abstract: The first porous molecular conductor (PMC), which exhibits porosity, a through-space conduction pathway and rich charge carriers (electrons), was prepared through electrocrystallization from Cd2+ and N,N′-di­(4-pyridyl)-1,4,5,8-naphthalenetetracarboxdiimide (NDI-py). [Cd­(NDI-py)­(OH2)4]­(NO3)1.3±0.1·nDMA (PMC-1) was assembled by π–π stacking among one-dimensional (1D) linear coordination polymers. The NDI cores were partially reduced into radical anions to form conductive π-stacked columns, yielding (1.0–3.3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 49 publications
(54 reference statements)
3
73
1
1
Order By: Relevance
“…Another study reported a porous Cd II material with the N , N ′-di(4-pyridyl)-1,4,5,8-naphthalenetetracarboxdiimide (DPNDI) linker. 90 The structure is a π–π stacked assembly of linear [Cd(OH 2 ) 4 (DPNDI)] polymers, which arrange into a hexagonal framework. The interlayer stacking distance is remarkably short, at only 3.18 Å (compared to typical distances of ∼3.3 Å for napthalenediimide (NDI)-based molecules).…”
Section: Through-space Pathwaysmentioning
confidence: 99%
“…Another study reported a porous Cd II material with the N , N ′-di(4-pyridyl)-1,4,5,8-naphthalenetetracarboxdiimide (DPNDI) linker. 90 The structure is a π–π stacked assembly of linear [Cd(OH 2 ) 4 (DPNDI)] polymers, which arrange into a hexagonal framework. The interlayer stacking distance is remarkably short, at only 3.18 Å (compared to typical distances of ∼3.3 Å for napthalenediimide (NDI)-based molecules).…”
Section: Through-space Pathwaysmentioning
confidence: 99%
“…[139] Otherwise, some recents tudiesh ave proposed NDI-based MOFs exhibiting electrical conductivity upon partial reduction. [140,141] For example, aC d-NDI MOF exhibiting porositya nd high electrical conductivity( 10 À3 Scm À1 )w as obtained by electrocrystallization.T he mechanism was based on at hrough-space approach in which NDI moieties were partially reduced into radical anionsf orming p-stacked columns with high chargec arrier densities. [140] The use of NDI buildingb locks for the construction of COFs has been focused on organic electrodes for energy storagea pplications,t aking advantage of the electrochemical properties (Scheme 6).…”
Section: Naphtalene Diimide (Ndi)mentioning
confidence: 99%
“…In addition, ligand-based oxidation of dual-ion cathodes including CuTCNQ and NiDI have been investigated in the past two years. [61,62,65] Above results illustrate that mixed conductive CPs are the promising materials for rocking chair battery systems.…”
Section: Batterymentioning
confidence: 72%
“…Recently, a sextuple ordered interpenetrated CuÀ NDI frameworks exhibit an impressing electronic conductivity up to 1.2 × 10 À 3 S cm À 1 . [62] reported a three dimensional frameworks composed of Fe III and mixed-valence ligand of dhbq. [63] The synthesized crystal named as (NBu 4 ) 2 À Fe 2 (dhbq) 3 could be reduced to Na 0.9 (NBu 4 ) 1.8 Fe 2 (dhbq) 3 via the transformation of dhbq 2À to dhbq 3À .…”
Section: Mixed-valence Ligandsmentioning
confidence: 99%
See 1 more Smart Citation